Kinship, Cooperation, and the Evolution of Moral Systems. Issue 2 (10th January 2019) - Enke, Benjamin
Abstract: Across the social sciences, a key question is how societies manage to enforce cooperative behavior in social dilemmas such as public goods provision or bilateral trade. According to an influential body of theories in psychology, anthropology, and evolutionary biology, the answer is that humans have evolved moral systems: packages of functional psychological and biological mechanisms that regulate economic behavior, including a belief in moralizing gods; moral values; negative reciprocity; and emotions of shame, guilt, and disgust. Based on a stylized model, this article empirically studies the structure and evolution of these moral traits as a function of historical heterogeneity in extended kinship relationships. The evidence shows that societies with a historically tightly knit kinship structure regulate behavior through communal moral values, revenge taking, emotions of external shame, and notions of purity and disgust. In loose kinship societies, on the other hand, cooperation appears to be enforced through universal moral values, internalized guilt, altruistic punishment, and an apparent rise and fall of moralizing religions. These patterns point to the presence of internally consistent but culturally variable functional moral systems. Consistent with the model, the relationship between kinship ties, economic development, and the structure of the mediating moral systems amplified over time.